2011
DOI: 10.1007/s10561-011-9254-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the use of glycerol preserved and cryopreserved allogenic skin for the treatment of severe burns: differences in clinical outcomes and in vitro tissue viability

Abstract: Cryopreserved (CryoPA) and Glycerol-preserved (GPA) skin allografts are commonly used in the treatment of severe burn injuries. However, comparable data on their differences in clinical outcome is scarce. This retrospective review aims to study the effect of allograft viability on clinical outcomes. The records of 48 severe burn patients who either received CryoPA or GPA were reviewed. Key burn mortality determinants were used to match the 2 groups. Clinical outcomes such as mortality rate (MR) and the length … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 43 publications
0
17
0
1
Order By: Relevance
“…In addition, in our study we utilized a cryoprotectant in order to improve the cell survival rate in cryopreservation. Similar as other authors 22,34,35 , the glycerol was utilized as cryoprotectant once this molecule enter the cells, reduce the ice crystal formation, thereby protecting cells from freezing lesion.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…In addition, in our study we utilized a cryoprotectant in order to improve the cell survival rate in cryopreservation. Similar as other authors 22,34,35 , the glycerol was utilized as cryoprotectant once this molecule enter the cells, reduce the ice crystal formation, thereby protecting cells from freezing lesion.…”
Section: Discussionmentioning
confidence: 76%
“…However, in recent study comparing the use of glycerol preserved and cryopreserved allogenic skin for the treatment of severe burns, the histological structural integrity observed that cryopreservation confirmed to be the more viable product 34 . Thus, questions about the possibility of cryopreservation for longer periods (up to 1 year) encouraged this study in terms of long-term cryopreservation.…”
Section: Discussionmentioning
confidence: 99%
“…CPA was carried out in a pre-warm 0.9% saline solution to thaw and rinsed away three times to remove cryoprotectant. Also GPA was rehydrated by soaking in saline solution at room temperature for 10 min and rinsed away three times [11].…”
Section: Keratinocyte Cell Viabilitymentioning
confidence: 99%
“…Second, GPA refers to a method in which tissues are put in 85% Glycerol and the refrigerated at 2˚C -8˚C. This allograft is said to serve as a mechanical and physiological barrier and reduce the loss of protein and moisture, thereby preventing the bacterial infection [10] [11]. However, even though many studies have reported that skin protect pathogen by secreting the anti-microbial peptide (AMP) such as defensin, there has been very little research reported on the direct anti-microbial effectiveness of allograft.…”
mentioning
confidence: 99%
“…From their experience with burns, difficult wounds and leg ulcers, various authors agree that higher viability is associated with better wound-bed preparation and graft taking. 13,17,[33][34][35] Viable CSAs are deemed to have better transplant performance, to promote neovascularization, speed up healing, stimulate immunomodulatory response and reduce mortality risk. 13,14,[31][32][33][34][35][36] Some authors speculate that high cell viability may not be necessary for skin allograft function as a temporary dressing or permanent substitute.…”
mentioning
confidence: 99%